Hemisynapse Formation Between Target Astrocytes and Cortical Neuron Axons in vitro - Teng, Zenghui; Gottmann, Kurt (Frontiers in Molecular Neuroscience, 2022)
One of the most fundamental organizing principles in the mammalian brain is that neurons do not establish synapses with the other major cell type, the astrocytes. However, induced synapse formation between neurons and astrocytes appears conceivable, because astrocytes are well known to express functional ionotropic glutamate receptors. Here, we attempted to trigger synapse formation between co-cultured neurons and astrocytes by overexpressing the strongly synaptogenic adhesion protein LRRTM2 in astrocytes physically contacted by cortical axons. Interestingly, control experiments with immature cortical astrocytes without any overexpression resulted in the induction of synaptic vesicle clustering in contacting axons (hemisynapse formation). This synaptogenic activity correlated with the endogenous expression of the synaptogenic protein Neuroligin1. Hemisynapse formation was further enhanced upon overexpression of LRRTM2 in cortical astrocytes. In contrast, cerebellar astrocytes required overexpression of LRRTM2 for induction of synaptic vesicle clustering in contacting axons. We further addressed, whether hemisynapse formation was accompanied by the appearance of fully functional glutamatergic synapses. We therefore attempted to record AMPA receptor-mediated miniature excitatory postsynaptic currents (mEPSCs) in innervated astrocytes using the whole-cell patch-clamp technique. Despite the endogenous expression of the AMPA receptor subunits GluA2 and to a lesser extent GluA1, we did not reliably observe spontaneous AMPA mEPSCs. In conclusion, overexpression of the synaptogenic protein LRRTM2 induced hemisynapse formation between co-cultured neurons and astrocytes. However, the formation of fully functional synapses appeared to require additional factors critical for nano-alignment of presynaptic vesicles and postsynaptic receptors.